Studi Pendahuluan Uji Aktivitas Katalitik Katalis Montmorillonit K-10 Yang Dimodifikasi Cu2+ - Admi, Admi; Isnaini, Delvi; Syukri, Syukri (Universitas Andalas, 2024)
The current study examines the catalytic activity of Cu2+-exchanged cation montmorillonite K-10 (MMT K-10) catalyst, which synthesized by hydrothermal method. X-ray fluoressence (XRF) and X-ray Diffraction (XRD) were used for characterizing the newly synthesis catalyst. The effect of thermal activation on the support of MMT K-10 with a modifier Cu investigated on its catalytic performance for conversion waste cooking oil to produce fatty acid methyl ester (FAME) by transesterification reaction. Synthesis biodiesel was further characterized by Gas Chromatography-Mass Spectroscopy (GC-MS). The biodiesel was obtained at transesterification reaction conditions: 3% (w/w) catalyst loading, molar ratio of oil to methanol = 1:10, and 3 h of reaction time at 90°C. The yield of FAME of WCO for MMT K-10, MMT K-10/Cu2+, MMT K-10 (activation 110°C)/Cu2+, MMT K-10 (activation 300°C)/Cu2+ catalysts were the 9,47%; 10,36%; 10,41%; and 12,01% of FAME, respectively. This study exhibites that the activation of thermal on the support MMT K-10 which modified by Cu2+ leads to reduction of the crystal size. The decreasing crystal size contributes on increasing catalytic performance of the heterogeneous catalyst.